SIKAP PILIHAN BAHASA PELAKU EKONOMI BERDASARKAN TINJAUAN UNDANG-UNDANG DAN PERATURAN PEMERINTAH - Eka Dian Savitri; Kartika Nuswantara; Siti Zahrok (Institut Teknologi Sepuluh Nopember, 2016)
This is a descriptive qualitative study that aims to describe Indonesian economists language attitude, specifically on the way they label the products.By means of behaviorist approach, the study raises an interpretation of the economists throughot observation. In order to come to the answer of the problem, data employed in this present study is the secondary data derived from other researchers. Then, the analysis of the data is employed by reviewing the labeling process in three ways, namely reasons for labeling, characteristics of the language attitude, and the Act 24 year 2009. It is figured out that there are 29 products labeled using foreign words or phrase, and the rest 11 products useIndonesia language. The phenomenon shows that labeling in foreign languages would enhance the positive image of the product. On the other hand, positive attitude is shown by the economists through their loyalty using bahasa Indonesia for labelling. Final finding is to show that the attitude displays the conterproductive to the Act 24 of 2009.